Intestinal colonization with extended-spectrum beta-lactamase producing Enterobacterales (ESBL-PE) during long distance travel: A cohort study in a German travel clinic (2016–2017). Issue 33 (January 2020) - ; Sin, Muna Abu; Antão, Esther-Maria; Behnke, Michael; Bleidorn, Jutta; Boklage, Evgeniya; Eckmanns, Tim; Forstner, Christina; Gastmeier, Petra; Gensichen, Jochen; Gropmann, Alexander; Hagel, Stefan; et al.
Abstract: Background: Intercontinental travel contributes to the spread of extended-spectrum beta-lactamase producing Enterobacterales (ESBL-PE). We assessed risk factors for intestinal ESBL-PE colonization in people travelling to low and middle income countries in the tropics and subtropics to better understand how travel affects ESBL-PE spread. Method: This prospective cohort study in travellers attending a travel clinic in Leipzig, Germany was conducted in 2016–2017. Information on risk factors related to travel, symptoms, antibiotic use, health care usage, accommodation, destination, diet and hygiene was collected by questionnaire after travel. Stools were phenotypically tested for ESBL-PE before and after travel. Risk factors for ESBL-PE colonization were identified using logistic regression. Results: Of the 230 travellers that were ESBL-PE negative before travelling, 23% (n = 53) travellers returned positive. Multivariable analyses showed that age, type of accommodation and travelling to Asia were associated with ESBL-PE colonization. Conclusions: Given that a considerable amount of travellers returned with ESBL-PE, we recommend raising awareness in returning high-risk travellers, e.g. those returning from high-risk areas. They should be aware that they may carry antimicrobial-resistant bacteria after travel, and how they can prevent its spread. The role of the type of accommodation as a factor favouring intestinal colonization with ESBL-PE requires further investigation.